Public Health, Yellow Fever, and the Making of Modern Tampico - Kuecker, Glen (Urban History Review / Revue d'histoire urbaine, 2008)
This essay uses the Mexican port city of Tampico as a case study of the relationship between nation-state formation, urban transformation, and public health policy during the late nineteenth century. It examines a virulent yellow fever epidemic in 1898 to illustrate how Tampico's urban transformation generated conditions for the epidemic, and how public health officials addressed the challenge of combating the epidemic. Special emphasis is placed on how officials used quarantines in a failed attempt to contain the problem. As a result of its limitations, national authorities came to perceive quarantines as antithetical to the project of the modern nation-state, leading them to adopt urban sanitation projects as substitute. Local and state authorities, however, retained their faith in the quarantine, often out of a desperate need to protect their populations and commerce. The battle against yellow fever constituted part of an important shift in public health authority from the control of local officials to national authorities, which further consolidated the power of the nation-state. The essay concludes with consideration of the implications of Tampico's 1898 epidemic for a history of circum-Caribbean port cities.